MODELING THE PHYSICAL EDUCATION PROCESS USING HEALTH-IMPROVING TOOLS - Behzod Bakhtiyorovich Atavullaev (American Journals, 2026)
This work is devoted to the study of the problem of modeling the educational process in physical education using means of health promotion. During the study, two groups were formed: an experimental group (training was conducted on the basis of a program that provided for the acquisition of in-depth knowledge of health preservation and strengthening methods and the use of various health promotion tools in the structure of the annual cycle) and a control group (training was conducted on the basis of a generally accepted program). As a result of the work carried out, the effectiveness of the experimental program was proven.
Keywords: Program, health, physical education lesson, control group